2008
DOI: 10.1061/(asce)0742-597x(2008)24:3(128)
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Partnering Success through an Incentive Agreement: Lessons Learned from an Underground Railway Extension Project in Hong Kong

Abstract: Over the years, it has been observed that partnering has been ineffectively implemented in the public sector of Hong Kong. Contributing factors to this lack of success are nature and large size of bureaucratic organizations and commercial pressure compromising the partnering attitude. The Mass Transit Railway Corporation Limited (MTRCL), one of the prominent pioneers in adopting project partnering in the infrastructure sector of Hong Kong since 1999, however, implemented the partnering principle with significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 6 publications
0
31
0
Order By: Relevance
“…Given the fact that TCC/GMP schemes are extensively applied in infrastructure projects worldwide including Hong Kong (Walker et al, 2002;Rojas and Kell, 2008;Chan et al, 2008;Bogus et al, 2010;Chan et al, 2010a), the findings of this study should be relevant and essential to both construction academics and industrial practitioners in the field of infrastructure development and management. The research study has engendered some research evidence to capture the lessons learned from previous TCC/GMP construction projects for generating best practice guidelines for equitable (preferred) risk allocation in future target cost-based projects especially in those infrastructure developments often associated with high risks, both locally and overseas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the fact that TCC/GMP schemes are extensively applied in infrastructure projects worldwide including Hong Kong (Walker et al, 2002;Rojas and Kell, 2008;Chan et al, 2008;Bogus et al, 2010;Chan et al, 2010a), the findings of this study should be relevant and essential to both construction academics and industrial practitioners in the field of infrastructure development and management. The research study has engendered some research evidence to capture the lessons learned from previous TCC/GMP construction projects for generating best practice guidelines for equitable (preferred) risk allocation in future target cost-based projects especially in those infrastructure developments often associated with high risks, both locally and overseas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chan et al (2008) also evaluated the effectiveness of partnering on an underground railway extension project with TCC arrangement in Hong Kong via another study, recommending both partnering and TCC to be the essential ingredients of project success. Kaplanogu and Arditi (2009) explored the practice of pre-project peer reviews in construction companies of the United States, suggesting that this kind of review was critical in reducing the risk of a proposed new GMP project.…”
Section: Nicolinimentioning
confidence: 99%
See 1 more Smart Citation
“…Partnership with key stakeholders refers to the establishment of a strong relationship with key stakeholders involved in a programme (Chan et al, 2008). These stakeholders include designers, contractors and suppliers involved in a construction megaproject.…”
Section: Core Capacitymentioning
confidence: 99%
“…A case study of a GMP project launched by Rose and Manley (2007) in Australia revealed that one of the negative drivers of implementing the financial incentive mechanism was inequitable risk allocation, based on their interview data and opinions. On the other hand, the case studies conducted by both Chan et al (2008a) and Chan et al (2010b) demonstrated that the projects with the GMP and TCC forms of arrangement were completed within budget and ahead of schedule. These previous successes should reinforce the confidence in procuring GMP/TCC contracts by the Hong Kong respondents.…”
Section: Item 11: Provide a Dispute Resolution Mechanism By Way Of Admentioning
confidence: 99%